Associations between the CNTNAP2 gene, dorsolateral prefrontal cortex, and cognitive performance on the Stroop task. (20th February 2017) - Zhu, Bi; Chen, Chuansheng; Xue, Gui; Lei, Xuemei; Wang, Yunxin; Li, Jin; Moyzis, Robert K.; Li, Jun; Dong, Qi; Lin, Chongde
Highlights: The CNTNAP2 genetic variations were associated with DLPFC volume and surface area. Subjects with greater left DLPFC surface area had better cognitive performance. Left DLPFC surface area mediated the association between CNTNAP2 and cognition. Abstract: The CNTNAP2 (contactin-associated protein-like 2) gene, highly expressed in the human prefrontal cortex, has been linked with autism and language impairment. Potential relationships between CNTNAP2, dorsolateral prefrontal cortex (DLPFC), and cognition have been suggested by previous clinical studies, but have not been directly examined in the same study. The current study collected structural MRI, genetic, and behavioral data in 317 healthy Chinese adults, and examined associations between CNTNAP2 variants, DLPFC, and cognitive performance (measured by the Stroop task). After controlling for intracranial volume, sex, and age, the CNTNAP2 genetic polymorphism at SNP rs7809486 had the strongest association with bilateral DLPFC volume ( p  = 0.00015 and 0.00014 for left and right DLPFC volumes, respectively), with GG homozygotes having greater bilateral DLPFC volumes and surface areas than the other genotypes. Furthermore, TT homozygotes of CNTNAP2 rs4726946 (a nearby SNP that had moderate linkage disequilibrium with rs7809486) had greater left DLPFC volume and surface area, and better cognitive performance than the other genotypes. Subjects with greater left DLPFC surface area had better cognitive performance. Importantly, the left DLPFC surface area mediated the association between the CNTNAP2 rs4726946 genotype and cognitive performance. This study provides the first evidence for associations among the CNTNAP2 gene, left DLPFC structure, and cognitive control.